The influence mechanism underlying meaning in life on career adaptability among college students: a chain intermediary model - Lin, Zhengzheng (Frontiers in Psychology, 2024)
The coronavirus disease 2019 has posed a huge challenge to the career situation of university students. The study aimed to understand the mechanism underlying the meaning in life on career adaptability among college students during the COVID-19 pandemic. A quantitative method was adopted. 1,182 university students were surveyed using the meaning in life questionnaire, simplified coping style questionnaire, adult general hope scale and career adapt-abilities scale. There was a significant positive correlation between meaning in life, positive coping styles, hope, and career adaptability. Positive coping styles and hope play a separate mediating role and a chain mediating role. The findings of the study emphasise the importance of meaning in life to enhance the career adaptability. At the same time, positive coping styles and increased levels of hope contribute to the development of career adaptability among college students.